2017
DOI: 10.1111/all.13371
|View full text |Cite
|
Sign up to set email alerts
|

Indoor allergen levels in settled airborne dust are higher in day‐care centers than at home

Abstract: Mite, mouse, cat, and dog allergens were mostly higher in DCC than in homes. Exposure to dog and cat allergens in DCC often reached levels of households with pets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…With the development of antigen‐specific IgE antibodies, MC and basophils become sensitized and can recognize environmental allergens. In asthma, the key allergens of importance include house dust mites, animal dander, and mold 56,57 …”
Section: Type 2 Immunity In the Lung And Skinmentioning
confidence: 99%
“…With the development of antigen‐specific IgE antibodies, MC and basophils become sensitized and can recognize environmental allergens. In asthma, the key allergens of importance include house dust mites, animal dander, and mold 56,57 …”
Section: Type 2 Immunity In the Lung And Skinmentioning
confidence: 99%
“…63 In addition to residential environments, indoor air quality in nonresidential buildings (e.g., schools) plays an important role in respiratory health. [64][65][66] The Schools Indoor Pollution and Health:…”
Section: Other Sources Of Indoor Air Pollutionmentioning
confidence: 99%
“…63 In addition to residential environments, indoor air quality in nonresidential buildings (e.g., schools) plays an important role in respiratory health. [64][65][66] The Schools Indoor Pollution and Health: Observatory Network in Europe (SINPHONIE) project, funded by the European Parliament, assessed indoor air exposure in schools in 23 countries. 67 The study found that PM 2.5 , some VOCs (e.g., formaldehyde), radon, and allergens (especially molds) were commonly present.…”
Section: (B) (B) (C) (A)mentioning
confidence: 99%
“…2 9 It is passively transferred on clothing 2,5,19 ; as a result, the allergen is ubiquitous and has been documented in homes without cats, private vehicles, and public transportation and buildings at levels (≥8 µg Fel d 1 per gram of dust) that exceed threshold value associated with sensitization. 2,5,7,[25][26][27][28][29][30][31][32][33][34] Although Fel d 1 levels in schools are detectable, they are often low and may not induce symptoms, 35 but a Swedish study found that indirect exposure to cat may be associated with worsening of asthma in cat-allergic students. 26…”
Section: Fel D1 the Ma Jor C At Allerg Enmentioning
confidence: 99%